KARAKTERISTIK MATERI PEMBELAJARAN TARI UNTUK MAHASISWA ASING - Lesa Paranti; Utami Arsih; Indrawan Nur Cahyono; Ani Nur Auliyatun Latifah (Universitas Sultan Ageng Tirtayasa, 2023)
The internationalization carried out by Indonesian universities has become a trend favored by students both from within and outside the country. The internationalization program offered to foreign students at Universitas Negeri Semarang is precisely the dance class, because through dance they learn about Indonesian arts and culture. This study aimed to examine the dance learning program for foreign students at Universitas Negeri Semarang and find the concept of dance learning materials that are suitable for the needs and characteristics of foreign students. The method used in this study is a qualitative method. Collecting data using interviews, observation, and documentation. Data analysis techniques include data reduction, data presentation, and verification. The data validity technique uses triangulation of sources, methods, and theories. The results showed that the purpose of learning dance for foreign students is that students are able to get to know Indonesian culture through the practice of local dance arts. There are long-term and short-term dance learning programs. This affects the determination of the dance material being studied. The characteristic of dance material for foreign students includes: 1) the theme according to the local wisdom of the local area; 2) dance moves are sourced from local traditional dances but need to be adapted to the abilities and characteristics of the culture where students come from; 3) thick musical accompaniment with nuances and characteristics of local arts; 4) the duration of the dance is not too long, ideally 3-5 minutes. This concept is the basis for the preparation of dance scripts. The dance concepts and scripts that have been compiled can be used as guidelines for creating dance materials that are in accordance with the characteristics and learning programs for foreign students at Universitas Negeri Semarang